Achieving Optimal Medical Therapy: Insights From the ORBITA Trial - Michael Foley; Christopher A. Rajkumar; Matthew Shun‐Shin; Sashiananthan Ganesananthan; Henry Seligman; James Howard; Alexandra N. Nowbar; Thomas R. Keeble; John R. Davies; Kare H. Tang; Robert Gerber; Peter O’Kane; et al. (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease, 2021)
Background In stable coronary artery disease, medications are used for 2 purposes: cardiovascular risk reduction and symptom improvement. In clinical trials and clinical practice, medication use is often not optimal. The ORBITA (Objective Randomised Blinded Investigation With Optimal Medical Therapy of Angioplasty in Stable Angina) trial was the first placebo‐controlled trial of percutaneous coronary intervention. A key component of the ORBITA trial design was the inclusion of a medical optimization phase, aimed at ensuring that all patients were treated with guideline‐directed truly optimal medical therapy. In this study, we report the medical therapy that was achieved. Methods and Results After enrollment into the ORBITA trial, all 200 patients entered a 6‐week period of intensive medical therapy optimization, with initiation and uptitration of risk reduction and antianginal therapy. At the prerandomization stage, the median number of antianginals established was 3 (interquartile range, 2–4). A total of 195 patients (97.5%) reached the prespecified target of ≥2 antianginals; 136 (68.0%) did not stop any antianginals because of adverse effects, and the median number of antianginals stopped for adverse effects per patient was 0 (interquartile range, 0–1). Amlodipine and bisoprolol were well tolerated (stopped for adverse effects in 4/175 [2.3%] and 9/167 [5.4%], respectively). Ranolazine and ivabradine were also well tolerated (stopped for adverse effects in 1/20 [5.0%] and 1/18 [5.6%], respectively). Isosorbide mononitrate and nicorandil were stopped for adverse effects in 36 of 172 (20.9%) and 32 of 141 (22.7%) of patients, respectively. Statins were well tolerated and taken by 191 of 200 (95.5%) patients. Conclusions In the 12‐week ORBITA trial period, medical therapy was successfully optimized and well tolerated, with few drug adverse effects leading to therapy cessation. Truly optimal medical therapy can be achieved in clinical trials, and translating this into longer‐term clinical practice should be a focus of future study. Registration URL: https://www.clinicaltrials.gov; Unique identifier: NCT02062593.